2022
DOI: 10.1115/1.4055853
|View full text |Cite
|
Sign up to set email alerts
|

Ontology Network-Based In-Situ Sensor Selection for Quality Management in Metal Additive Manufacturing

Abstract: Metal additive manufacturing (MAM) offers a larger design space with greater manufacturability than traditional manufacturing has offered. Despite continued advances, MAM processes still face huge uncertainty, resulting in variable part quality. Real-time sensing for MAM processing helps quantify uncertainty by detecting build failure and process anomalies. While the high volume of multidimensional sensor data—such as melt pool geometries and temperature gradients—is beginning to be explored, sensor selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This method could not fully explain more complex situations and could not relate simulation parameters with printing parameters. Other researchers have found that the process variant affects the as-built qualities [29][30][31][32][33][34][35][36][37][38][39]; they have indicated that the process plays a significant role in determining the anisotropic mechanical behaviors. However, there still lacks a linkage between such effects and morphing behaviors.…”
Section: State-of-the-art Reviewmentioning
confidence: 99%
“…This method could not fully explain more complex situations and could not relate simulation parameters with printing parameters. Other researchers have found that the process variant affects the as-built qualities [29][30][31][32][33][34][35][36][37][38][39]; they have indicated that the process plays a significant role in determining the anisotropic mechanical behaviors. However, there still lacks a linkage between such effects and morphing behaviors.…”
Section: State-of-the-art Reviewmentioning
confidence: 99%
“…Besides the abovementioned experimental analysis for developing a qualitative relationship between the process and the desired quality, other researchers used the data analytical methods [ 45 ], and machine learning model [ 46 , 47 , 48 ] to provide a probabilistic predictive model for providing guidance in assuring the as-built quality in the pre-processing stage. However, few researchers developed a novel multi-dimensional process-quality framework [ 49 , 50 , 51 , 52 , 53 ] that can provide a quantitative relation between the multiple process parameter and the build quality and provide a certain printable zone to control the quality as desired.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite having its origins in the Semantic Web, ontology has found widespread use in numerous other domains. In the field of AM, Liu and Rosen [24] presented an ontology-based knowledge representation and reuse method for AM process design; Witherell et al [25] built several ontology-based metamodels for reusing AM process models; Roh et al [26] constructed several ontology-based laser and heat metamodels for metal AM; Lu et al [27] proposed an ontology-based digital solution for integrated and collaborative AM; Dinar and Rosen [28] constructed a general ontology for AM design; Hagedorn et al [29] developed an ontology-based approach for creative design in AM; Liang [30] established an ontology-based knowledge framework for AM process design; Kim et al [31] constructed an AM design ontology to facilitate analysis of manufacturability; Sanfilippo et al [32] built an ontology-based model for AM; Ali et al [33] constructed an ontology that represents product life cycle knowledge in AM; Xiong et al [34] developed an ontology-based process design platform for wire arc AM; Ko et al [35] studied construction of rules for AM design based on ontology and machine learning; Chen et al [36] constructed an ontology-based Bayesian network model to represent the causal links between AM design and process parameters, as well as structure and mechanical properties; Roh et al [37] established an ontology-based process map capturing all data in a metal AM process chain; Mayerhofer et al [38] developed an ontology that represent the information regarding the capabilities of AM processes, materials, and machines; Li et al [39] developed an ontology for knowledge representation in LPBF process planning; Roh et al [40] created network-based ontologies that capture the relationship between process variables and sensor data in real-time, as well as the relationship between as-built component characteristics and related physical phenomena; Hasan et al [41] established an ontological framework for process defects knowledge modelling in LPBF; Park et al [42] presented an ontology-based framework to facilitate collaborative knowledge management in the identification of data analytics opportunities in AM; Wang et al [43] built an ontology-supported embedding learning system for defect diagnosis in AM; Wang et al [44] developed an ontology for eco-design in AM that incorporates informative sustainability analysis. It is clear that ontologies not only support the representation of AM part data themselves, but, most importantly, have the capabilit...…”
Section: Introductionmentioning
confidence: 99%